Principles of materials circular economy - Ramakrishna, Seeram; Rajan, Jose (Cell Press, 2022)
Material sourcing, processing, usage, and end-use management play a substantial role in present-day life; however, the sustainability concerns call for adaptation of “materials circular economy” to provide the materials’ share of the solutions to the existential threats. This Matter of Opinion puts together ten principles of materials circular economy as a guide for the materials community at large, including researchers, engineers, designers, manufacturers, businesses, and policy makers, to review and update. We hope that these ten principles and associated future editions will be helpful to eliminate the materials-related existential threats.